2017
DOI: 10.1016/j.amepre.2017.06.019
|View full text |Cite|
|
Sign up to set email alerts
|

Transactions at a Northeastern Supermarket Chain: Differences by Supplemental Nutrition Assistance Program Use

Abstract: Introduction Although one in seven Americans receives Supplemental Nutrition Assistance Program (SNAP) benefits, little is known on how these benefits for food are spent because individual-level sales data are not publicly available. The purpose of this study is to compare transactions made with and without SNAP benefits at a large regional supermarket chain. Methods Sales data were obtained from a large supermarket chain in the Northeastern U.S. for a period of 2 years (April 2012–April 2014). Multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
(28 reference statements)
1
18
1
Order By: Relevance
“…Use of SNAP benefits was not significantly related to HEI outcomes. This runs contrary to one recent study of transactions involving specific food items within a Northeastern supermarket chain that found select unhealthy foods more likely to be purchased with SNAP benefits (Franckle et al, 2017), as well as to broader public policy discourse that often associates SNAP use with unhealthy purchasing (Barnhill, 2011; Chrisinger, 2017; Leung et al, 2013; Long et al, 2014). Still, this finding raises questions about why and how SNAP fell short of delivering on its namesake promise of “nutrition,” and possible avenues for improvement, such as the modest success of the Healthy Incentives Pilot, which offered participants additional SNAP bonuses when purchases were made on eligible healthy items (Bartlett et al, 2014; Klerman et al, 2014; Wilde et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Use of SNAP benefits was not significantly related to HEI outcomes. This runs contrary to one recent study of transactions involving specific food items within a Northeastern supermarket chain that found select unhealthy foods more likely to be purchased with SNAP benefits (Franckle et al, 2017), as well as to broader public policy discourse that often associates SNAP use with unhealthy purchasing (Barnhill, 2011; Chrisinger, 2017; Leung et al, 2013; Long et al, 2014). Still, this finding raises questions about why and how SNAP fell short of delivering on its namesake promise of “nutrition,” and possible avenues for improvement, such as the modest success of the Healthy Incentives Pilot, which offered participants additional SNAP bonuses when purchases were made on eligible healthy items (Bartlett et al, 2014; Klerman et al, 2014; Wilde et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…913 These findings could be explained by poorer dietary quality of SNAP participants. Compared to non-participants, SNAP participants consume more refined grains, processed meats, and sugar-sweetened beverages (SSBs) and fewer F&V. 13–15 An analysis of recent sales data from a large supermarket chain demonstrated that over two years (2012–2014) in 188 northeast store locations, 13% of SNAP spending, and 19% of non-SNAP spending, was for F&V. 16 Additionally, transactions made with SNAP benefits included greater spending on less healthful food categories, including SSBs (5.5% vs. 3.7%) and red meat (16.9% vs. 11.5%), than those made with non-SNAP dollars. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Thirty-four studies were included in this scoping review [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Information on customer purchasing assessment methodologies used across studies is shown in ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies included in this review ( n = 19, 55.9%) examined SES differences in consumer food and/or beverage purchases [ 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 39 , 42 , 43 , 45 , 49 , 50 , 51 , 52 , 54 ]. These findings underscore that identifying purchasing patterns by SES continues to be a major priority in the field; included studies generally showed a lower likelihood of fruit, vegetable, and whole grain purchases and a higher likelihood for discretionary product purchases (i.e., salty snacks, sweets, and SSB) among consumers with lower incomes compared to higher incomes [ 58 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%